2016
DOI: 10.14341/dm7674
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of endothelial monocyte activating polypeptide-II in type 1 diabetes patients with microangyopathy and arterial hypertention.

Abstract: (5.23 ± 1.66 ng/ml and 1.25 ± 0.76ng/ml; respectively, р < 0.01) and with the group of patients with diabetes but without hypertension (5.23 ± 1.66 ng/ml and 3.63 ± 1.9 ng/ml; respectively, р < 0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Therefore, advancing our understanding of the effects of age‐associated diseases such as T2D and HTN on cytokine responses during prolonged work represents an emerging area of interest. Previous findings demonstrate that serum EMAP‐II concentrations are higher in individuals with T2D independently of obesity 22 and in individuals with type 1 diabetes 21 . Conversely, we show that baseline serum EMAP‐II concentrations are similar between healthy older men with and without T2D or HTN.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Therefore, advancing our understanding of the effects of age‐associated diseases such as T2D and HTN on cytokine responses during prolonged work represents an emerging area of interest. Previous findings demonstrate that serum EMAP‐II concentrations are higher in individuals with T2D independently of obesity 22 and in individuals with type 1 diabetes 21 . Conversely, we show that baseline serum EMAP‐II concentrations are similar between healthy older men with and without T2D or HTN.…”
Section: Discussioncontrasting
confidence: 65%
“…Conversely, we show that baseline serum EMAP‐II concentrations are similar between healthy older men with and without T2D or HTN. The factors underlying these discordant findings remain unclear, however, Mogylnytska and Mankovsky 22 also showed that serum EMAP‐II positively correlated with hemoglobin A1c, blood glucose, body mass index, and several blood lipids, suggesting that EMAP‐II concentrations may be modulated by the progression or severity of disease states. Additionally, our findings demonstrate that the presence of T2D blunts the EMAP‐II response to prolonged moderate‐intensity exercise performed in the heat relative to older men with and without HTN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a comorbidity significantly increases the risk of severe cardiovascular complications [4][5]. The presence of hypertension in patients with type 1 diabetes is associated with an increase in the frequency of severe stages of diabetic nephropathy and retinopathy; on the other hand, diabetes significantly increases the risk of emergence and developing hypertension, and hypertension is associated with a high risk of insulin resistance and metabolic abnormalities [6]. When combined with hypertension and diabetes, the risk of CHD developing increases by 2-4 times, stroke -2-3 times, visual loss -10-25 times, renal insufficiency -15-20 times, gangrene of the lower extremities -20 times [7].…”
Section: Introductionmentioning
confidence: 99%